Ice-rafted debris as a source of non-conservative behaviour for the εNd palaeotracer - Vogt-Vincent, Noam; Lippold, Jörg; Kaboth-Bahr, Stefanie (Dr.); Blaser, Patrick (Geo-Marine Letters, 2020)
Neodymium isotopic composition (epsilon Nd) has enjoyed widespread use as a palaeotracer, principally because it behaves quasi-conservatively in the modern ocean. However, recent bottom water epsilon Nd reconstructions from the eastern North Atlantic are difficult to interpret under assumptions of conservative behaviour. The observation that this apparent departure from conservative behaviour increases with enhanced ice-rafted debris (IRD) fluxes has resulted in the suggestion that IRD leads to the overprinting of bottom water epsilon Nd through reversible scavenging. In this study, a simple water column model successfully reproduces epsilon Nd reconstructions from the eastern North Atlantic at the Last Glacial Maximum and Heinrich Stadial 1, and demonstrates that the changes in scavenging intensity required for good model-data fit is in good agreement with changes in the observed IRD flux. Although uncertainties in model parameters preclude a more definitive conclusion, the results indicate that the suggestion of IRD as a source of non-conservative behaviour in the epsilon Nd tracer is reasonable and that further research into the fundamental chemistry underlying the marine neodymium cycle is necessary to increase confidence in assumptions of conservative epsilon Nd behaviour in the past.